Upaya Meningkatkan Kreativitas Siswa Melalui Pendekatan Kontruktivisme pada Materi Cahaya dan Sifatnya di Kelas V Sekolah Dasar Negeri 104/IX Kedemangan - M. Nurdiyansyah; Ilyas Idris (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This research is a Classroom Action Research (CAR), with the background of SDN 104/IX Kedemangan. The object of this research is the fifth grade students of SDN 104/IX Kedemangan, and the purpose of this research is to apply the constructivism approach in improving students' creativity in the material of light and properties. This research was conducted in three cycles and four stages, including: (1) planning, (2) action, (3) observation and (4) reflection. Data were obtained through observation, interviews and documents. Using qualitative analysis to analyze data, including data collection, data reduction, data presentation, drawing conclusions or verification. The results of the study indicate that the application of the constructivism approach can improve students' creativity in the learning process. The increase in students' creativity can be measured from the assessment of cycle I and assessment of cycle II. The value of student creativity in cycle I was 49.6%, and the value of student creativity in cycle II was 85%. Based on this increase, the results of the study at SDN 104/IX Kedemangan have been realized well.